Potencial evocado visual por flash em cães, ovinos e equinos - Palumbo, Mariana Isa Poci [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The visual evoked potential (VEP) is an electrodiagnostic test that detects and records the electrical activity in the visual central pathway. The VEP has applicability in veterinary neurology, but the test is not routinely used in Brazil. The aims of this study were obtain normative data of flash-VEP from dogs, sheep and horses. PEV were obtained with monopolar needle electrodes placed in O1 and O2 (active), Fpz (common reference) and Cz (ground). VEP obtained from 17 dogs, 17 sheep and 17 horses were included in the normative study. Both eyes were evaluated, totaling 34 results in each species. The most consistent result in all tests was an electropositive deflection, with a mean latency of 55.4 ms in dogs (P55), 63.75 ms in sheep (P63), and 52.76 ms in horses (P53). All tests also allowed the identification of 2 electronegative deflections: N31 and N75 in dogs, N42 and N86 in sheep, N38 and N72 in horses. The F-VEP was also performed in 3 horses before and during sedation with different doses of xylazine (0.4 and 1.1 mg/kg) or detomidine (0.005 and 0.014 mg/kg). Sedation significantly affected the results, even at the lower dose. It was concluded that the BAEP is a useful and safe test to evaluate the visual central pathway. The obtained data and methodology used in this study will be useful for comparison with the results obtained from animals with different injuries related to the central visual pathway

Potencial evocado visual (PEV) é um teste eletrodiagnóstico que capta e registra a atividade elétrica da via visual central. O PEV tem aplicabilidades na neurologia veterinária, mas o teste não é utilizado rotineiramente no Brasil. O objetivo desta tese foi padronizar o PEV por flash em cães, ovinos e equinos. Os PEV foram obtidos com a utilização de eletrodos de agulha monopolar posicionados em O1 e O2 (ativos), em Fpz (referência comum) e em Cz (terra). Os potenciais de 17 cães, 17 ovinos e 17 equinos foram incluídos no estudo normativo. Os dois olhos foram analisados, totalizando 34 exames em cada espécie. Foi possível identificar em todos os exames uma deflexão eletropositiva com latência média de 55,4 ms em cães (P55), 63,75 ms em ovinos (P63) e 52,76 ms em equinos (P53). Em todos os exames também foi possível a identificação de duas deflexões eletronegativas: N31 e N75 em cães, N42 e N86 em ovinos e N38 e N72 em equinos. O PEV também foi obtido de três equinos antes e durante a sedação com diferentes doses de xilazina (0,4 e 1,1 mg/kg) ou detomidina (0,005 e 0,014 mg/kg). A sedação influenciou significativamente nos registros, mesmo com doses baixas. Os dados obtidos e a metodologia utilizada neste estudo serão úteis para comparação com o exame de animais com diferentes lesões relacionadas com as vias visuais
Flash-visual evoked potential in dogs, sheep and horses
Keywords: Visão - Testes; Olhos - Doenças; Animais - Doenças; Neurologia veterinaria; Eye - Diseases and defects